Manufacturing bio-tiles - Horn, Emma (Department of Civil Engineering, 2025)
Bio-tiles are a biobased alternative to conventional tiles that utilise a promising low energy technology called microbially induced calcium carbonate (CaCO3) precipitation (MICP). This work aimed to determine whether bio-tiles that meet the strength requirements of conventional ceramic tiles could be met using the ureolysis MICP pathway. The ureolytic activity of Sporosarcina pasteurii was controlled by centrifuging and dilution with fresh yeast extract media. Bio-tiles can be made with MICP using various methods, each with drawbacks and advantages. Three methods were tested: submersion, pumping and combining the benefits of both into a third that is more automated, modular and scalable: binder jet 3D printing. The submersion method had custom moulds submerged in cementation solution that contained all the calcium and urea required for the MICP reaction for 7 days. For this reactor system, a low optimum bacteria activity (4.0 mmol/L·min) and CaCO3 precipitation rate constant was identified (0.11–0.18 day−1). However, the process required additives such as 0.3 M magnesium chloride to achieve bio-tiles that met international standards. The pumping method was only operated for 4 days. With this technique, cementation solution was pumped through custom sealed moulds at intervals. The highest tested effective urease activity of 40 mmol NH4-N/L·min of S. pasteurii was found to be most beneficial to the breaking strength of the bio-tiles. Pre-seeding of the geotextiles with CaCO3 was explored and the mass of seeds initially present on the geotextiles was found to offer significant improvement to the breaking strength of 21-82%, increasing with seed loading. These bio-tiles were able to far exceed the required strength standards. With the automated production technique, a binder jet 3D printing prototype, it was found that 3 wt.% freeze-dried bio-slurry, 8 days of operation and supplementary magnesium allowed the formation of bio-tiles that met internal strength standards. A supplement of 0.3 M magnesium chloride almost tripled the breaking strength of bio-tiles produced with the automated technique. While additional seeding with CaCO3 crystals had minimal effect on breaking strength, it was beneficial for enhancing the formation of bio-tiles at corners and edges. The process's scalability makes it suitable for commercial applications, where large volumes of bio-tiles could theoretically be produced with reduced operational costs. In summary, this research has shown for the first time that bio-tiles grown using MICP and multiple techniques can achieve a breaking strength and modulus of rupture that meets international standards, provided key conditions are met. This comprehensive investigation into MICP-based bio-tile production demonstrates the potential for innovative bio-materials to revolutionise the construction industry by offering sustainable, cost-effective, and high-performance alternatives to traditional materials. The findings provide a foundation for future research and development efforts aimed at optimising the production processes, enhancing the mechanical properties, and scaling up the manufacturing of bio-tiles for widespread commercial use. With the uptake of bio-tiles, there is potential to decarbonise an age-old industry and reduce dependence on fossil fuels, and other construction materials can now follow.